Noncommutative Geometry and Number Theory
DOI: 10.1007/978-3-8348-0352-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Holomorphic bundles on 2-dimensional noncommutative toric orbifolds

Abstract: Abstract. We define the notion of a holomorphic bundle on the noncommutative toric orbifold T θ /G associated with an action of a finite cyclic group G on an irrational rotation algebra. We prove that the category of such holomorphic bundles is abelian and its derived category is equivalent to the derived category of modules over a finite-dimensional algebra Λ. As an application we finish the computation of K 0 -groups of the crossed product algebras describing the above orbifolds initiated in [17], [28], [29]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…The author thanks Jianmin Chen for the reference [14] and Guodong Zhou for the reference [1]. The author is very grateful to Zengqiang Lin for pointing out several misprints and to David Ploog for many helpful suggestions.…”
Section: Acknowledgmentsmentioning
confidence: 96%
“…The author thanks Jianmin Chen for the reference [14] and Guodong Zhou for the reference [1]. The author is very grateful to Zengqiang Lin for pointing out several misprints and to David Ploog for many helpful suggestions.…”
Section: Acknowledgmentsmentioning
confidence: 96%
“…In [4] (using work of Polishchuk [15]) we showed that the homomorphism T 3 is an injective map on K 0 (A κ θ ) = Z 8 in the case that θ is irrational -and in the rational case we would have to include Connes' cyclic 2-cocycle that picks out the "label of the trace". Based on the values in Table 2 of [3, (page 37)], 9 the unbounded traces ψ k of Cubic invariant projections take values in the following lattice in the complex plane…”
Section: ρ(E(t)) = E(t) κ(E(t)) = E(t);mentioning
confidence: 99%
“…Then the group Z 2 acts on E by the rule (x : y : z) → (x : −y : z). By a result of Geigle and Lenzing [17, Proposition 4.1 and Example 5.8], see also [33,Corollary 1.4], there is a derived equivalence…”
Section: Non-commutative Curves With Nodal Singularitiesmentioning
confidence: 99%